TINJAUAN YURIDIS TERHADAP TANAH TERLANTAR MENURUT PERATURAN PEMERINTAH NOMOR 11 TAHUN 2010 TENTANG PENERTIBAN DAN PENDAYAGUNAAN TANAH TERLANTAR - Haerani Husainy; Diah Astri Ellisa (Maleo Law Journal, 2017)
The State grants the right to a person or legal entity always accompanied by the obligations set forth in the LoGA and the right granting authority. Therefore, the holder of the right is prohibited from abandoning the land, and if the right holder abandons the land then the BAL has regulated the legal consequences of the abolition of the land rights concerned and the termination of legal relations and affirmed as land directly controlled by the state. The criteria for determining the land has been abandoned, both under the BAL and also the government regulation are substantially the same as abandoned land objects including land rights. These lands are not cultivated, unused or utilized in accordance with the circumstances or nature, the purpose of granting the rights or the basis of their control. Therefore the soil should be maintained.Keywords : abandoned land, Lae Effect